Penerapan Regresi Linier Ganda untuk Mengukur Efisiensi Pola Penggunaan Air Tanah System Rice Intensification (SRI) di Kabupaten Bandung, Subang, dan Karawang - Iwa Sungkawa (Bina Nusantara University, 2015)
This paper discusses the application of multiple linear regression to measure the efficiency and success of the pattern of groundwater using System of Rice Intensification. The purpose of this paper is to provide an overview of the procedures and the use of multiple linear regression analysis and to measure the impact of independent variables (habits of farmers P3A) in the use of groundwater. Multiple Linear Regression analysis is used to examine the relationships and dependencies between farmers habits P3A to the efficiency of water use patterns of SRI. The results show that the success and efficiency groundwater use is recommended in SRI pattern depends on the habits and behavior of the P3A farmers use ground water for their farming needs.